Distinct clinical and genetic mutation characteristics in sporadic and Lynch syndrome-associated endometrial cancer in a Chinese population. (August 2021) - Sun, Peisong; Shen, Yan; Wang, Tian; He, Ya; Zhang, Ye; Tian, Wei; Yang, Binkai; Hu, Yuanjing
Highlights: Young age and non-obese were two clinical characteristics specific to suspected LS-associated EC patients. The sporadic and suspected LS-associated EC groups had 43 and 59 specific mutated genes, respectively. MASP2, NADK and RNF223 gene might be regarded as the biomarkers of EC. Abstract: Background: The diagnosis of Lynch syndrome-associated endometrial cancer patients is significant for early warning of their relatives. The purpose of this study was to provide diagnostic indicators of Lynch syndrome-associated endometrial cancer by screening the differential clinical and genetic characteristics. Methods: Clinical information and hysterectomy specimens were collected from 377 eligible patients with endometrial cancer. The MLH1 methylation level was detected by an EZ DNA Methylation-Gold Kit. According to the above experimental results, the patients were then divided into sporadic endometrial cancer and suspected Lynch syndrome-associated endometrial cancer groups. A total of 62 samples were randomly selected for whole-exome sequencing. IBM SPSS Statistics 21 was used to compare the clinical data between the sporadic and suspected Lynch syndrome-associated endometrial cancer groups, and the relationship between the specific high-frequency-mutation genes and the clinical data. Results: According to the results of MMR immunohistochemistry and MLH1 methylation, the sporadic endometrial cancer group included 361 patients and the suspected Lynch syndrome-associated endometrial cancer group included 16 patients in this study. In the clinical analysis, the average age of the suspected Lynch syndrome-associated endometrial cancer patients was 45.50 ± 11.50 years, which was significantly younger than the 51.17 ± 10.03 years of the sporadic endometrial cancer patients (P = 0.028). The average BMI of the suspected Lynch syndrome-associated endometrial cancer patients was 23.43 kg/m 2 (CI: 20, 30), which was lower than the 26.50 kg/m 2 of the sporadic endometrial cancer patients (P = 0.028). Combined with the WES data, MASP2, NADK and RNF223 were identified as three specific mutation sites related to age, FIGO stage and histology. Conclusions: Compared with the suspected endometrial cancer patients, the Lynch syndrome-associated endometrial cancer patients were younger and less obese. Mutations in MASP2, NADK and RNF223 might be regarded as genetic endometrial cancer features related to clinical characteristics.